THE EFFECT OF REWARD SYSTEM, WORK MOTIVATION AND WORK FACILITIES ON EMPLOYEE PERFORMANCE IN LUBUK BAJA DISTRICT - Suharto, Andi Muhammad; Herman, Henry; Sudianto, Sudianto (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyse the influence of the reward system, work motivation, and work facilities on employee performance in the Lubuk Baja District, Batam City. This study's background is grounded in the deteriorating quality of public services attributed to insufficient work motivation, an ineffective reward system, and inadequate work facilities. The research employed a quantitative methodology utilising a survey technique. The sample consisted of 35 Lubuk Baja District employees, and data analysis was conducted through multiple linear regression using SPSS version 25. The results of the study indicate that the reward system partially has a positive and significant effect on employee performance (p=0.010; beta=0.312). Work motivation also has a considerable positive impact (significance 0.004; regression coefficient 0.327), as do work facilities (significance 0.016; regression coefficient 0.284). Simultaneously, the three independent variables have a positive and significant effect on employee performance (F-count 42.753; significance 0.000 < 0.05). The coefficient of determination (R²) of 0.787 indicates that these three variables explain 78.7% of the variation in employee performance, with the remaining 21.3% explained by factors outside this study. These findings confirm that improving employee performance requires a holistic approach that combines an effective reward system, high work motivation, and adequate work facilities.